2021
DOI: 10.1111/area.12692
|View full text |Cite
|
Sign up to set email alerts
|

Dune gardening? A critical view of the contemporary coastal dune management paradigm

Abstract: Modern coastal dune management is viewed largely through the prism of dune ecology. Achieving maximum biodiversity and preserving priority species are the primary objectives and management is based on interventions (grazing, mowing, burning, reseeding, and artificial destabilisation) to achieve that purpose. Under non-managed conditions, dune vegetation tends to evolve temporally following well-established succession patterns that lead to a low diversity scrub or woodland. Achieving high diversity involves res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 31 publications
(24 reference statements)
0
14
0
Order By: Relevance
“…Compared to terrestrial ecosystems, because of the environmental and microclimatic conditions, they have selected peculiar and specialised fauna and flora, often also exclusive (Gracia et al, 2019;Fabbri et al, 2021). Furthermore, these environments represent important ecological corridors for the animals in the coastal environment (Cooper and Jackson, 2020). This habitat exclusivity involves the coexistence of multiple elements of different biogeographical origins, united by high levels of specialisation.…”
Section: An Ecological Restoration Planmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to terrestrial ecosystems, because of the environmental and microclimatic conditions, they have selected peculiar and specialised fauna and flora, often also exclusive (Gracia et al, 2019;Fabbri et al, 2021). Furthermore, these environments represent important ecological corridors for the animals in the coastal environment (Cooper and Jackson, 2020). This habitat exclusivity involves the coexistence of multiple elements of different biogeographical origins, united by high levels of specialisation.…”
Section: An Ecological Restoration Planmentioning
confidence: 99%
“…It creates high, hummocky peaked dunes, which can easily withstand flooding and erosion (Seabloom et al, 2013;Bruls et al, 2016). Even the practice of sprinkling the dunes with the beached remains of Posidonia and other beached sea herbs has given good results, as these are natural materials widely available on site and which rapidly decompose without leaving traces or requiring restoration work (De Falco et al, 2003;Ruiz and Romero, 2003;Corenblit et al, 2007;Balestri et al, 2012;Cooper and Jackson, 2020;Maiolo et al, 2020). Recent studies demonstrated that planting mangroves along the shore or beach can reduce the wave height by 50% to 99% (McIvor et al, 2012;Raju and Arockiasamy, 2022).…”
Section: An Ecological Restoration Planmentioning
confidence: 99%
“…Particular damage is linked to environmental impoverishment, resulting in around 77% of annual habitat losses and 38% of annual economic losses due to destruction of beaches and dunes [56,57]. It is estimated that 45% of Mediterranean coastal dunes have been damaged or destroyed since 1900, while the remaining 55% have lost some natural characteristics [58]. In Southern Europe, loss of 2000-17,000 km 2 of coastlines, and their heritages, and an estimated economic loss of EUR 18 billion are projected for the period 1908-2080 [59].…”
Section: Main Consequencesmentioning
confidence: 99%
“…There are some excellent recent papers that highlight contributions in these spaces, for example, the exploration of emerging hybrid urban landforms (Dixon et al, 2017), the provocative characterisation of the coastal management of dunes as “dune gardening” (Cooper & Jackson, 2021), and discussion around the role of public participation in river management (Buletti Mitchell & Ejderyan, 2021). The latter study touches on ideas explored by Lane (2019) in relation to critical physical geography and the integrative study of human–environment interactions, an area around which we would welcome further submissions.…”
Section: What Area Is and Is Notmentioning
confidence: 99%